Intracellular ROS scavenging and antioxidant regulation of WL15 from cysteine and glycine-rich protein 2 demonstrated in zebrafish in vivo model - Guru, Ajay; Lite, Christy; Freddy, Allen J.; Issac, Praveen Kumar; Pasupuleti, Mukesh; Saraswathi, N.T.; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Arshad, Aziz; Arockiaraj, Jesu (Developmental and comparative immunology, 2021)
Antioxidant peptides are naturally present in food, especially in fishes, and are considered to contain rich source of various bioactive compounds that are structurally heterogeneous. This study aims to identify and characterize the antioxidant property of the WL15 peptide, derived from Cysteine and glycine-rich protein 2 (CSRP2) identified from the transcriptome of a freshwater food fish, Channa striatus. C. striatus is already studied to contain high levels of amino acids and fatty acids, besides traditionally known for its pharmacological benefits in the Southeast Asian region. In our study, in vitro analysis of WL15 peptide exhibited strong free radical scavenging activity in 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), superoxide anion radical and hydrogen peroxide (H2O2) scavenging assay. Further, to evaluate the cytotoxicity and dose-response, the Human dermal fibroblast (HDF) cells were used. Results showed that the treatment of HDF cells with varying concentrations (10, 20, 30, 40 and 50 μM) of WL15 peptide was not cytotoxic. However, the treatment concentrations showed enhanced antioxidant properties by significantly inhibiting the levels of free radicals. For in vivo assessment, we have used zebrafish larvae for evaluating the developmental toxicity and for determining the antioxidant property of the WL15 peptide. Zebrafish embryos were treated with the WL15 peptide from 4 h of post-fertilization (hpf) to 96 hpf covering the embryo-larval developmental period. At the end of the exposure period, the larvae were exposed to H2O2 (1 mM) for inducing generic oxidative stress. The exposure of WL15 peptide during the embryo-larval period showed no developmental toxicity even in higher concentrations of the peptide. Besides, the WL15 peptide considerably decreased the intracellular reactive oxygen species (ROS) levels induced by H2O2 exposure. WL15 peptide also inhibited the H2O2-induced caspase 3-dependent apoptotic response in zebrafish larvae was observed using the whole-mount immunofluorescence staining. Overall results from our study showed that the pre-treatment of WL15 (50 μM) in the H2O2-exposed zebrafish larvae, attenuated the expression of activated caspase 3 expressions, reduced Malondialdehyde (MDA) levels, and enhanced antioxidant enzymes, including superoxide dismutase (SOD) and catalase (CAT). The gene expression of antioxidant enzymes such as glutathione S-transferase (GST), glutathione peroxide (GPx) and γ-glutamyl cysteine synthetase (GCS) was found to be upregulated. In conclusion, it can be conceived that pre-treatment with WL15 could mitigate H2O2-induced oxidative injury by elevating the activity and expression of antioxidant enzymes, thereby decreasing MDA levels and cellular apoptosis by enhancing the antioxidant response, demonstrated by the in vitro and in vivo experiments. [Display omitted] •WL15, a peptide from cysteine and glycine-rich protein 2 (CSRP2) of a teleost was identified.•WL15 possessed antioxidant and radical scavenging capacity.•WL15 treated HDF cells and human erythrocytes showed no cytotoxicity.•Pre-treatment of WL15 reduced intracellular ROS and attenuated the apoptotic response induced by H2O2 in zebrafish larvae.•WL15 increased the expression of antioxidant enzyme genes (GST, GPx and GCS) in zebrafish larvae.